2020
DOI: 10.1002/adfm.201909708
|View full text |Cite
|
Sign up to set email alerts
|

Giant Strain Control of Antiferromagnetic Moment in Metallic FeMn by Tuning Exchange Spring Structure

Abstract: Manipulation of the antiferromagnetic moment in antiferromagnets (AFMs) is a crucial issue for developing AFM‐based spintronic devices. Lattice strain is an effective strategy to modulate the antiferromagnetic moment and is traditionally based on a direct crystalline tailoring of AFMs. A novel method for strain tuning the antiferromagnetic moment by controlling the exchange spring in the AFM, which is applicable to other conventional AFM materials, is reported. Specifically, a TiNi(Nb) shape memory alloy (SMA)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(12 citation statements)
references
References 44 publications
0
12
0
Order By: Relevance
“…This effect was explained by the appearance of the AFM domain walls parallel to the interface. In addition, the observed features can be useful for developing novel methods [ 44 ] for tuning the exchange spring in the AFM.…”
Section: Discussionmentioning
confidence: 99%
“…This effect was explained by the appearance of the AFM domain walls parallel to the interface. In addition, the observed features can be useful for developing novel methods [ 44 ] for tuning the exchange spring in the AFM.…”
Section: Discussionmentioning
confidence: 99%
“…Researchers have demonstrated that AFM order exchange‐coupled to an FM can be magnetically controlled via the exchange spring effect at the AFM/FM interface. [ 26–30 ] This phenomenon has been explored in tunneling anisotropic magneto‐resistance (MR) devices [ 31–34 ] , in which the binary state of AFM switches as a function of magnetization in the adjacent FM layer. [ 34 ] This issue is of importance for AFM/FM‐based SOT devices, due to the fact that AFM order at the interface could be modified electrically via SOT.…”
Section: Introductionmentioning
confidence: 99%
“…[24,25] Moreover, Young's moduli of common metallic SMA are comparable with that of the magnetic films, facilitating effective strain transfer in tuning the electronic structure of the film significantly. [26,27] In this study, we successfully realized strainmanipulated creation and annihilation of skyrmions in [Pt/Co/ Ta] n multilayers by temperature control of the phase transition in a TiNiNb-SMA substrate. The strain effectively promoted the creation of skyrmion by lowering the nucleation field from 400 Oe to zero.…”
Section: Introductionmentioning
confidence: 99%